Marketing Strategy Analysis of PT Andiarta Muzizat (Ninja Express) in Maintaining Sustainability in Gunungsitoli City - Darwin Cornelius Ismet Zendrato; Otanius Laia (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
In the era of globalization and increasingly fierce business competition, companies are required to have a strong marketing strategy to survive and thrive in a dynamic market. The sustainability of a company is the key to its long-term success. The purpose of this study is to determine the marketing strategy and to identify internal and external factors that can influence the business sustainability of PT Andiarta Muzizat (Ninja Express) in Gunungsitoli City. The type of research used is a qualitative research approach. The sampling technique used is purposive sampling with 3 informants. Data collection techniques used are observation, documentation and interviews. Meanwhile, data analysis techniques used are data collection, data reduction, data presentation and drawing conclusions. From the results of the study, it was obtained that based on the analysis of marketing strategies, internal and external factors that influence the sustainability of Ninja Express's business in Gunungsitoli City, it can be concluded that the company needs to take concrete steps to ensure their growth and sustainability in the logistics and freight forwarding market. Marketing strategies involving collaboration in local events, trade exhibitions, active interaction on social media, special offers, and improved customer service have been recognized as appropriate steps. By maintaining a focus on customer satisfaction, partnering with local communities, customizing delivery services to suit consumer needs, and leveraging social media, Ninja Express can strengthen their brand visibility in Gunungsitoli City.